Information and Systems - Howarth Anne (Financial Times Management, 1999)
Information of Systems, Introduction, Managing in the Information Revolution, Gaining Competitive Advantage with Information Systems, Analysing Your Information Needs, Developing Information Systems, Impementing and Running Systems, References.